Perfect match - Picoult, Jodi (New York : Atria Books, 2007)
Whereas most parents lie awake at night vividly conjuring the worst scenarios that could befall their children in their absence. Nina lives the reality of such crisis-and it's her job to do something about them.
National College of Business and Arts
Keywords: Married women -- Fiction; Domestic fiction